Evidence-Based Advances in Rodent Medicine - Jekl, Vladimir; Hauptman, Karel; Knotek, Zdenek (The veterinary clinics of North America. Exotic animal practice, 2017)
The number of exotic companion pet rodents seen in veterinary practices is growing very rapidly. According to the American Veterinary Medical Association's surveys, more than 2,093,000 pet rodents were kept in US households in 2007 and in 2012 it was more than 2,349,000 animals. This article summarizes the most important evidence-based knowledge in exotic pet rodents (diagnostics of the hyperadrenocorticism in guinea pigs, pituitary tumors in rats, urolithiasis in guinea pigs, use of itopride as prokinetics, use of deslorelin acetate in rodents, cause of dental disease, and prevention of mammary gland tumors in rats).
Keywords: lékařská praxe založená na důkazech; morčata; Animals; veterinární lékařství; Guinea Pigs; Guinea pig; Female; nemoci hlodavců; zvířata; Evidence-Based Practice; Veterinary Medicine; Dental disease; Mammary gland tumor; Rat; Rodent Diseases; Deslorelin; ženské pohlaví